Scientific Style in English - Alencar, Marcelo S., 1957- (River Publishers series in innovation and change in education., 2017)
Style is a distinctive manner of expression, in writing or speech. The word evolved from Latin stilus, an instrument for writing, marking, or incising, such as something used by the ancients in writing on clay or waxed tablets. It is the way in which something is said or done, as distinguished from its substance. Style is also a convention with respect to spelling, punctuation, capitalization, and typographic arrangement and display followed in writing or printing. Scientific Style in English aims to help students with the reading and writing of scientific and technical texts in English, with a particular focus on style, grammar and math. It can be used by students and professionals with basic or intermediate understanding of the English language. Technical topics discussed in the book include: * Scientific Style in English * Mathematical Style in English * Technical Style * Stylistic Problems in English * How to write Theses and Dissertations.